Pengaruh Sistem Pembayaran Tunai dan Non-Tunai Terhadap Keputusan Pembelian pada Bakso Mekar Jaya di Jalan Harmonika Baru - Syahreza, M.; Amelia, Wan Rizca (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the influence of cash and cashless payment systems on purchasing decisions at Bakso Mekar Jaya, located on Jalan Harmonika Baru. With the increasing use of cashless payment systems across various sectors, it is essential to understand how consumer preferences in choosing payment methods impact their purchasing decisions. This research employs a quantitative approach using multiple linear regression analysis processed through SPSS 26. Data were collected through questionnaires distributed to 96 respondents who are customers of Bakso Mekar Jaya. The results indicate that both cash and cashless payment systems have a positive and significant effect on purchasing decisions. Cashless payment is perceived as more practical and efficient, while cash remains the preferred choice for some consumers who feel more comfortable with traditional methods. Therefore, business owners are advised to provide diverse payment options to enhance customer experience and foster consumer loyalty.